Evaluating the impact of COVID-19 pandemic on the physicians' psychological health: A systematic scoping review - Guraya, Shaista S.; Menezes, Prianna; Lawrence, Isabell Nelson; Guraya, Salman Yousuf; Rashid-Doubell, Fiza (Frontiers in Medicine, 2023)
Background COVID-19 has endangered healthcare systems at multiple levels worldwide. Published data suggests that moral dilemmas faced during these unprecedented times have placed physicians at the intersections of ethical and unethical considerations. This phenomenon has questioned the physicians' morality and how that has affected their conduct. The purpose of our review is to tap into the spectrum of the transforming optics of patient care during the pandemic and its impact on psychological wellbeing of physicians. Methods We adopted the Arksey and O'Malley's framework, defining research questions, identifying relevant studies, selecting the studies using agreed inclusion and exclusion criteria, charting the data, and summarizing and reporting results. Databases of PubMed/Medline, Web of Science, Scopus, Science Direct, CINAHL, and PsycInfo were searched using a predefined search string. The retrieved titles and abstracts were reviewed. Later, a detailed full-text analysis of the studies which matched our inclusion criteria was performed. Results Our first search identified 875 titles and abstracts. After excluding duplicates, irrelevant, and incomplete titles, we selected 28 studies for further analysis. The sample size in 28 studies was 15,509 with an average size of 637 per study. Both quantitative and qualitative approaches were used, with cross-sectional surveys being utilized in all 16 quantitative studies. Using the data from semi-structured interviews, several discrete codes were generated, which led to the identification of five main themes; mental health, individual challenges, decision-making, change in patient care, and support services. Conclusion This scoping review reports an alarming rise in psychological distress, moral injury, cynicism, uncertainty, burnout, and grief among physicians during the pandemic. Decision-making and patient care were mostly regulated by rationing, triaging, age, gender, and life expectancy. Poor professional controls and institutional services potentially led to physicians' crumbling wellbeing. This research calls for the remediation of the deteriorating mental health and a restoration of medical profession's advocacy and equity.